Caring for the Body, Building the Soul: Integrating Islamic Values into Traditional Bubus Medicine of the Sasak People of Lombok - Lalu Nasrulloh; Sumarsi Sumarsi; Khatipah; Mulyono (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to examine the integration of Islamic values in the traditional Bubus healing practices of the Sasak people of Lombok as a form of local wisdom that combines medical, spiritual, and cultural dimensions. Bubus is a concoction made from rice starch and wild plants that is processed into pills, then dissolved in water and sprinkled over the patient's entire body while reciting a Sasak mantra that begins with the basmalah. This study uses a qualitative approach with ethnographic methods. The primary data sources are three belian from Montong Baan Selatan Village, Terara Village, and Darmasari Village, plus local religious and traditional leaders as secondary data. Data collection was carried out through in-depth interviews, participatory observation, and documentation, then analyzed using thematic analysis. The findings show that Bubus is not merely a traditional medical practice, but rather a knowledge system that organically combines the values of tawakkal (trust in God), syukur (gratitude), amanah (trustworthiness), and rahmatan lil alamin (mercy for all creation) in a single healing ritual. This study confirms that Islam has naturally integrated into the local wisdom of the Sasak people, making Bubus a medium for Islamic character education that is alive in the community.